ANALISIS FAKTOR PENENTU KESULITAN BELAJAR DAN PENGARUHNYA TERHADAP HASIL BELAJAR PADA MATA PELAJARAN IPS TERPADU SISWA KELAS VII SMPN DI KECAMATAN SUNGAI GERINGGING - Nadia Rista (Jurusan Ekonomi Pembangunan Fakultas Ekonomi Universitas Negeri Malang, 2019)
This research purpose to identify and analysis: (1) What is the factors that make learning difficulties in the subjects of IPS Integrated Student Class VII SMPN in Sungai Geringging, (2) Which factors are the most dominant as a determinant of learning difficulties in the subjects of IPS Integrated Student Class VII SMPN in Sungai Geringging, (3) The effect of learning diffiuculties on learning outcomes in the subjects of IPAS Integrated Student Class VII SMPN in Sungai Geringging. The method used in this research is factor analysis and multiple regression analysis. The results shows that (1) the determinants of learning difficulties consisted of 17 indicators divided into 3 variables: (a)interpersonal limitations and disruptions in the learning process, (b)supplement support, and (c)readiness of students in learning , (2) The most dominant factor as a determinant of student learning difficulties is the relationship between student with the value communality 0.718, (3)Learning difficulties significantly influence the learning outcomes for student Class VII SMPN in Sungai Geringging.